'If they can say it they can write it': Inclusive pedagogies for senior secondary physical education. Issue 5 (3rd May 2016) - Garrett, Robyne; Wrench, Alison
Abstract : Pedagogical practices are fundamental to teachers' work, and in the spaces of schooling impact significantly on students' success and achievement (Evans, J. 1986. Physical Education, Sport and Schooling: Studies in the Sociology of Physical Education . London: Falmer Press.). This is especially the case for students from disadvantaged backgrounds who are deeply reliant on schooling for their educational resources. This article explores the interrelationships between pedagogical practices, the physical education curriculum at the senior secondary level and learning by both students and a teacher in a school located in an area of socio-economic disadvantage. Action research investigating a pedagogical redesign of a unit of 'Skill Acquisition' is the specific focus. Of key interest are pedagogical practices that incorporated opportunities to learn 'about' Skill Acquisition 'through' and 'in' movement. These practices attempted to develop and apply scientific literacies specific to the human movement sciences, which are important for academic success in senior secondary physical education. Findings reveal high student engagement, increasing utilisation of scientific literacies and application of new learning to life-world situations. We argue that pedagogical practices that integrate learning 'about' 'through' and 'in' movement disrupt default modes of teaching theoretical concepts in physical education, which diminish opportunities for academic success amongst students from low-socio-economic backgrounds.